Descolonizando as propostas curriculares na educação infantil: uma análise sobre as relações étnico-raciais e de gênero - Ferreira, Solange Oliveira [UNIFESP] (2020)
This research aims to investigate the strategies of curriculum construction and organization in Early Childhood Education, bringing into the debate ethnic-racial and gender issues. It investigates the limits and challenges of organizing educational proposals based on commemorative dates, analyzing the possibilities of educational planning that deconstructs inequalities and represents Brazilian cultural diversity. Its theoretical framework is the fields of study: curricular guidelines in Early Childhood Education, Ethnic-racial and Gender. The qualitative research was developed from document analysis and semi-structured interviews with educational managers. The methodological proposal used the pedagogical documentation collected in an institution of Early Childhood Education, as a means of photographic supports representing fragments of the daily life of the institution, to support the interviews. The research seeks to provide subsidies for the construction of decolonizing curricular guidelines and indicators that contribute to the valorization of diversity and the constitution of gender identity and that gives visibility to ethnic-racial relations, respecting Brazilian childhoods and cultural plurality.